2018
DOI: 10.1055/s-0038-1641218
|View full text |Cite
|
Sign up to set email alerts
|

Findings from 2017 on Consumer Health Informatics and Education: Health Data Access and Sharing

Abstract: Patients understand the need for sharing information to facilitate best care and to enrich biomedical knowledge. When confronted with the reality of accessing information systems for their own information, patients are concerned about usability as well as privacy. Overall, there is a need for more emphasis on: 1) considering privacy as a feature defined by design; 2) using specific consent approaches and data sharing mechanisms for recruiting clinical trial participants; 3) taking into account socio-demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The analysis provided the principle of fairness in two dimensions which include fair access and procedural fairness [A 14 , 39 , 41 , 42 , 48 , 51 , 52 , 76 , 84 , 93 95 ]. Fairness in terms of fair access has to do with the requirements for users being allowed to look at and use the data [A 14 ], and should address concerns about fair or equitable access to data, research results, and public health benefits derived from those results [A 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis provided the principle of fairness in two dimensions which include fair access and procedural fairness [A 14 , 39 , 41 , 42 , 48 , 51 , 52 , 76 , 84 , 93 95 ]. Fairness in terms of fair access has to do with the requirements for users being allowed to look at and use the data [A 14 ], and should address concerns about fair or equitable access to data, research results, and public health benefits derived from those results [A 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…This sometimes means that Individuals should be provided with a simple and timely means to access and obtain their individually identifiable health information in a reliable form and format [A 42 ]. Governance frameworks may allow for information to be exchanged in certain scenarios including data subjects or research participants being able to access their own biomedical data e.g via patient portals to facilitate fair access [A 84 ]. However, how custodians or data stewards or even clinicians react to such access by patients and other data consumers need to be addressed in governance frameworks to promote fair access.…”
Section: Resultsmentioning
confidence: 99%
“…The finding that more patients were comfortable with social screening itself than with its documentation in the EHR is consistent with a recent study on social risk screening where participants reported concern with privacy and utilization of social risk data 33 and findings from other work describing patients' unease around sharing health data. 56,57 There are already calls for developing standards to protect social risk data in EHRs, 58 which is increasingly relevant in the context of new efforts to share data across sectors. 59,60 Qualitative findings presented in the companion paper in this supplement augment understanding of participant EHR-related concerns.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that the willingness to participate in biomedical research advertised on social media platforms and search engines, as well as the willingness to share digital data with researchers, have been affected by recent news on the misuse of such data [39]. However, research about willingness to share data in health social media is still in its infancy and hence, further research in this space within a participatory health paradigm is warranted [40].…”
Section: Data Privacy Security and Quality Assurance Are The Most Rmentioning
confidence: 99%